Characterization of the physical-mechanical and thermal behavior of a clay building unit designed with thermo-insulating attributes and a coffee cisco organic additive (2019)
This research is articulated from the clay framework as material wealth of the region of Norte de Santander, Colombia, and seeks to structure attributes of passive thermal cooling in a ceramic piece for low cost masonry type block cooked with physical, mechanical and thermals feasible characteristics for warm tropical weather conditions of 33 °C on average. This work is based on previous studies that explores the partitions structure morphology in Blocks H10 establishing a model of 6 horizontal cavities for low thermal conductivity and having oblique geometry partitions to interrupt heat conduction by direct thermal bridge inside of the constructive unit called Form-C, which is taken as the object of analysis, adding 5% organic coffee cisco additive in the 95% clay mixture to increase the porosity with a proportion that does not affect the deterioration of the mechanical properties and allow to optimize the thermal insulation capacity regarding to a traditional product. Methodologies: in the first phase, prototypes of Block H10 with Form-A are manufactured by extrusion at the laboratory level as a comparative witness of the properties of a standard piece and Form-C as a piece with thermo-insulating strategies to execute physical-ceramic, geometric evaluations of mechanical resistance and water absorption applying the Norma Técnica Colombiana 4017 for masonry units. In the second stage, simulations of temperature distribution and heat flow are prepared by finite element method in ANSYS R16 software to determine the incidence of the variables in the mixture on heat transfer. The results obtained from thermal simulations show an energy decrease of 1.5 °C on average in relation to Form-A. In conclusion, the use of agro industrial scraps and the implementation of passive design techniques in the ceramic piece generate added value in a product that can be industrialized with improvements in technological properties from a thermal efficiency perspective in construction ceramics.